Leadership in European digital policy: Future role and direction for the D9+ Group - Fredrik Erixon; Philipp Lamprecht; Erik Van der Marel; Vanika Sharma; Elena Sisto (European Centre for International Political Economy (ECIPE), 2022)
In this paper, we will discuss how Europe makes digital policy and how its digital economic performance can be improved. The focus is on the D9+ initiative. Launched in 2016 on the initiative of former Swedish trade minister, Ann Linde, nine countries with a particular interest in matters of the digital economy met to learn from each other and seek common ground on policy issues. On occasions, the D9+ Group has issued joint statements relating to regulatory initiatives in the EU. Since its founding, the group has expanded, and now also includes "guest countries", but it remains fundamentally an initiative of small and mid-sized open-oriented economies with a strong interest to exploit the economic power of digitalisation and new emerging technologies. The D9+ initiative is important and this paper argues that its work should expand and focus on expanding the scale and scope of digital technological change in the European economy while addressing risks that an over-powering regulatory approach to digital policies in Europe reduces the benefits of the digital transformation. Importantly, the D9+ Group has a special interest to promote digital openness and avoid the agenda for technology sovereignty and strategic autonomy sliding into digital protectionism. Finding the right direction of policy is of fundamental importance for Europe's long-run economic growth, and the D9+ Group should take a leadership role.
Keywords: 330; Electronic commerce; EU policy; EU states; Electronic Commerce; EU-Politik; EU-Staaten